2022
DOI: 10.25259/sni_1130_2021
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic brain metastasis from small-cell carcinoma of the urinary bladder

Abstract: Background: Small-cell carcinoma of the urinary bladder (SCCB) accounts for 1% of all bladder tumors. We present a rare case of hemorrhagic metastatic brain tumor from SCCB diagnosed by navigation-guided endoscopic biopsy. Case Description: A 76-year-old man presented with sudden onset of aphasia and right hemiplegia from 3 weeks previously. He had a medical history of prostate cancer and SCCB. Computed tomography showed a mixed density mass in the left basal ganglia. On magnetic resonance imaging, the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, only two previous reports have focused on the surgical treatment of SCNC of the urinary bladder for metastatic brain tumors thus far. 1 , 2 ) Isaka et al reported a case involving surgery performed for a metastatic lesion in the left frontal lobe, including radiological, intraoperative, and pathological findings. 1 ) In that case, intense tumor staining was noted from early in the arterial phase on angiography, and there was substantial intraoperative bleeding from the fine vessels consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, only two previous reports have focused on the surgical treatment of SCNC of the urinary bladder for metastatic brain tumors thus far. 1 , 2 ) Isaka et al reported a case involving surgery performed for a metastatic lesion in the left frontal lobe, including radiological, intraoperative, and pathological findings. 1 ) In that case, intense tumor staining was noted from early in the arterial phase on angiography, and there was substantial intraoperative bleeding from the fine vessels consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Maeshima et al presented a case of metastatic tumor of the basal ganglia that resulted in intratumoral hemorrhaging and required hematoma evacuation. 2 ) Moreover, Theodros et al reported that primary small intestine tumors as extrapulmonary SCNC were highly vascularized and associated with substantial difficulty achieving hemostasis. 3 ) It has been reported that metastatic brain tumors derived from lung cancer are prone to bleeding, 7 ) and metastasis from SCNC of the bladder may have similar clinical features to small-cell lung cancer brain metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations